YOUTH EMPOWERMENT THROUGH THE BASIC MECHANICAL ENGINEERING EDUCATION AND TRAINING PROGRAM (DIKLAT) AT THE HADAIDA TECHNICAL CENTER BEKASI JOB TRAINING CENTER - Muhammad Hanif; Samsir Hakim (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2022)
Research Objectives: To find out and obtain an overview of the stages and results of Youth Empowerment through the Basic Mechanical Engineering Education and Training Program by the Hadaida Technical Center for Job Training. Research method: Qualitative. Results: The empowerment stages carried out by the Hadaida Technical Center were considered successful, because they were directly proportional to the results obtained by empowered education and training alumni, not only in terms of mechanical engineering, but also in the religious field. So that the alumni become better than before. The composition of education and training at the Ahadaida Center is 75% practical and 25% theory. The stages used are the awareness stage, the ability transformation stage, and the intellectual ability improvement stage